Not Wholly Communion: Skepticism and the Instrumentalization of Religion in Stoker's Dracula - Purcell, Stephen (Christianity & literature, 2018)
A recurring theme in Dracula criticism is the assumption that, because Stoker's protagonists rely on Catholic sacraments and symbols, they represent Catholicism, High Church Protestantism, or a perverse variation thereof. The protagonists' adoption of Catholic sacramentality, however, lacks any accompanying moral or epistemological shiftStoker's protagonists never adopt Christian morality, nor do they transition from skepticism to faith. Rather, the protagonists instrumentalize Catholic sacramental objects, making them tools with which to exterminate vampires and to justify the hatred that underpins that task. The protagonists' relationship to the Communion wafer encapsulates their disregard for theology and their willingness to manipulate sacrament.